2019
DOI: 10.1186/s12913-019-4030-4
|View full text |Cite
|
Sign up to set email alerts
|

Explaining patient delay in healthcare seeking and loss to diagnostic follow-up among patients with presumptive tuberculosis in Tanzania: a mixed-methods study

Abstract: Background Delay in healthcare seeking and loss to diagnostic follow-up (LDFU) contribute to substantial increase in tuberculosis (TB) morbidity and mortality. We examined factors, including perceived causes and prior help seeking, contributing to delay and LDFU during referral to a TB clinic among patients with presumptive TB initially seeking help at the pharmacies in Dar es Salaam Tanzania. Methods In a TB clinic, a semi-structured interview based on the explanatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
1
31
2
Order By: Relevance
“…In south-east Ghana, more than a quarter of presumptive TB patients never submitted a sputum, and non-submission of sputum was most strongly associated with longer distance to the laboratory. Studies from Zimbabwe, India and Tanzania have also reported high pre-diagnosis loss-to-follow, 25%, 30.4% and 44% respectively [16][17][18], and some studies, including one from Ghana, showed that attending rural health clinics and long travel distance were risk factors for delay or pre-diagnosis loss to follow-up [7,10,17,19]. In contrast, pre-diagnosis attrition was lower in South Africa and China (5% and 11% respectively) [20,21], perhaps because in South Africa, sputum specimens are transported free to a central laboratory for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In south-east Ghana, more than a quarter of presumptive TB patients never submitted a sputum, and non-submission of sputum was most strongly associated with longer distance to the laboratory. Studies from Zimbabwe, India and Tanzania have also reported high pre-diagnosis loss-to-follow, 25%, 30.4% and 44% respectively [16][17][18], and some studies, including one from Ghana, showed that attending rural health clinics and long travel distance were risk factors for delay or pre-diagnosis loss to follow-up [7,10,17,19]. In contrast, pre-diagnosis attrition was lower in South Africa and China (5% and 11% respectively) [20,21], perhaps because in South Africa, sputum specimens are transported free to a central laboratory for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons given by participants for not submitting sputum were being too busy to go to the laboratory (58/116, 50.0%), feeling well so not seeing the need to do the test (19,16.4%), having no money to travel to do the test (17, 14.7%) and being unable to produce sputum (15, 12.9%).…”
Section: Reasons For Not Submitting Sputummentioning
confidence: 99%
“…In general, in Africa, the population does not consult a health professional when rst symptoms appear. In most cases, people use traditional medicine or self-medicate and only consult when the condition becomes life-threatening [32,33]. Also, most older adults in Africa do not have health insurance and they have to make out-of-pocket payments for healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…In general, in Africa, the population does not consult a health professional when rst symptoms appear. In most cases, people use traditional medicine or self-medicate and only consult when the condition becomes life-threatening [32,33]. Also, most older adults in Africa do not have health insurance and they have to make out-of-pocket payments for healthcare services.…”
Section: Discussionmentioning
confidence: 99%